Mengembangkan Kreativitas Melalui Media Sedotan Plastik pada Anak Kelompok B di TK Adrikna Apitaik Kecamatan Pringgabaya Kabupaten Lombok Timur - Tri Anita Wahyu Ningsih; Muazzar Habibi; I Made Suwasa Astawa; Baik Nilawati Astini (Indonesian Journal of Elementary and Childhood Education, 2022)
This research was motivated by the lack of creativity through the media of plastic straws for Group B children in at TK (kindergarden) Adrikna Apitaik, Pringgabaya Sub-District, East Lombok District. The purpose of this research was finding out how to develop creativity through plastic straws for children in group B at TK Adrikna Apitaik, Pringgabaya Sub-District, East Lombok District. This research is development research which is a type of descriptive qualitative research. The Subject in this study were 10 people in grup B. Data Collection techniques in this study were observation and documentation techniques. Technical analysis of the data in this study was qualitative descriptive. The resuls showed that the achievement of creativity development through plastic straw media in group B children increased by 48.36% from the average value in the pre-test test of 35.29% included in the criteria for not developing (BB), and the average value of post-test was 83.29% included in the category of developing as expected (BSH). The conclusion is the subject experienced the development of creativity through the media of plastic straws in group B children at TK Adrikna Apitaik, Pringgabaya Sub-District, East Lombok District.